2015
DOI: 10.1007/s10565-015-9306-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CYP3A4 inhibition and hepatotoxicity using DMSO-treated human hepatoma HuH-7 cells

Abstract: A human hepatoma cell line (HuH-7) was evaluated as a metabolically competent cell model to investigate cytochrome P450 3A4 (CYP3A4) inhibition, induction, and hepatotoxicity. First, CYP3A4 gene expression and activity were determined in HuH-7 cells under three culture conditions: 1-week culture, 3-week culture, or 1% dimethyl sulfoxide (DMSO) treatment. HuH-7 cells treated with DMSO for 2 weeks after confluence expressed the highest CYP3A4 gene expression and activity compared to the other two culture conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…CYP3A4 subfamily enzymes play a major role in the metabolism of~30% of clinically used drugs from almost all therapeutic categories [30][31][32]. As previously reported [33], this major P450 enzyme is involved in CPZ oxidative metabolism, which is active in CPZ-treated in HepaRG cells.…”
Section: Discussionmentioning
confidence: 63%
“…CYP3A4 subfamily enzymes play a major role in the metabolism of~30% of clinically used drugs from almost all therapeutic categories [30][31][32]. As previously reported [33], this major P450 enzyme is involved in CPZ oxidative metabolism, which is active in CPZ-treated in HepaRG cells.…”
Section: Discussionmentioning
confidence: 63%
“…Hepatocellular carcinoma (HCC) is one of the most malignant cancers all over the world, with the third cause of cancer mortality (Poon 2011 ; Liu et al 2015 ). A number of risk factors have been shown to drive this process, including hepatitis virus infections, non-alcoholic fatty liver diseases, and alcoholic liver diseases (Cavazza et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, HepG2 cells show poor metabolic enzymes such as CYP enzymes. 33,34 Researchers have attempted to create a stable cell line that expresses CYP enzymes to screen for hepatotoxicity, [35][36][37] as CYP expression is an important parameter for evaluating hepatotoxicity and drug metabolism under similar conditions as those in vivo. In this study, we confirmed that differentiated HepaRG cells express major drug-metabolizing enzymes.…”
Section: Discussionmentioning
confidence: 99%